Respiratory bronchiolitis‐associated interstitial lung disease secondary to electronic nicotine delivery system use confirmed with open lung biopsy. Issue 3 (3rd April 2017) - Flower, Mark; Nandakumar, Lakshmy; Singh, Mahendra; Wyld, David; Windsor, Morgan; Fielding, David
Abstract : As a modern phenomenon, there is currently limited understanding of the possible toxic effects and broader implications of electronic nicotine delivery systems (ENDS). Large volumes of aerosolized particles are inhaled during "vaping" and there are now an increasing number of case reports demonstrating toxic effects of ENDS, as well as human studies demonstrating impaired lung function in users. This article presents a case of respiratory bronchiolitis interstitial lung disease (RB‐ILD) precipitated by vaping in a 33‐year‐old male with 10 pack years of traditional cigarette and prior treatment for mixed germ cell tumour. The patient had started vaping 10–15 times per day while continuing to smoke 10 traditional cigarettes per day. After 3 months of exposure to e‐cigarette vapour, chest computed tomography demonstrated multiple new poorly defined pulmonary nodules with fluffy parenchyma opacification centred along the terminal bronchovascular units. Video‐assisted thoracoscopy with lung biopsy of the right upper and right middle lobes was undertaken. The microscopic findings were overall consistent with RB‐ILD. This case demonstrates toxicity with use of ENDS on open lung biopsy with resolution of radiographic findings on cessation. We believe that this is the first case where open lung biopsy has demonstrated this and our findings are consistent with RB‐ILD. Abstract : We believe this is an important case as it demonstrates clearly the direct toxic effects of the poorly understood electronic nicotine delivery system (ENDS). Further we believe this is the first case in the literature to demonstrate ENDS‐associated respiratory bronchiolitis interstitial lung disease (RB‐ILD) on open lung biopsy.